Precarious Work and its Impact on the Job Security: A Systematic Review during 2019-2023 - Espejo-Chacón, Luis Fernando; Zavala-Amézquita, Jose Junior; Manrique-Plácido, Juana Maribel; Pacheco-Torres, Julio Enrique; Gonzales-Renteria, Yuri Gagarín (Journal of Ecohumanism, 2024)
This study reviewed the literature on precarious work and its impact on job security for workers between 2019 and 2023, using databases such as Scopus, Dialnet, Google Scholar, Scielo, Latindex, and Redalyc. A systematic review methodology was employed with search terms like "precarious work," "precarious employment," "mental health," and "job security." The years with the highest number of publications were 2019 and 2021, both with 9 studies. The United States had the most research, and English predominated as the language of the studies. The most frequent keywords included "precarious work," "precarious employment," "mental health," and "precarity." The "International Journal of Environmental Research and Public Health" was the most relevant source, and most studies were original articles (82%). Precarious work was associated with both psychological and physical health issues, ranging from bodily injuries and poor quality of life to suicidal thoughts. The main factors affecting job security in precarious work include insecure jobs, low incomes, and inadequate work environments, leading to high job insecurity.